Management of Financial Performance Based on Capital Structure, Liquidity Ratio, Coverage and Activity - Jariah, Ainun; Lukiana, Ninik (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
All of Automotive companies, were quite badly affected during the Covid-19 pandemic. The automotive industry players do not simply surrender to this situation. As Idul Fitri 2020 approaches, the Association of Indonesian Automotive Industries (Gaikindo) synergizes with the Government to maintain the performance of the automotive industry. The situation improved as the Covid-19 cases in the country slumped. In 2020, wholesale sales for the automotive industry in Indonesia will only reach 530 thousand units. This figure is down by 50% from usual due to very limited mobility of people and goods. The automotive sector is gradually improving, car sales are picking up again in August 2021. In the first half of 2022, a number of automotive companies managed to score encouraging performances. This encouraging performance cannot be separated from funding decisions, availability of assets, ability to meet short and long term debts. Research objective to examine and analyze effect of capital structure, liquidity ratios, coverage and activity on financial performance. A total of 13 companies out of 16 automotive companies are listed Indonesia Stock Exchange for the period 2018 – 2021. Using hypothesis testing with multiple linear regression. The results showed only coverage ratio had an effect on financial performance. Novelty in this study uses two state conditions, namely before and during the Covid-19 pandemic.